Classi-fly inferring aircraft categories from open data - Strohmeier, M; Smith, MJ; Lenders, V; Martinovic, I (Association for Computing Machinery, 2021)
In recent years, air traffic communication data has become easy to access, enabling novel research in many fields. Exploiting this new data source, a wide range of applications have emerged, from weather forecasting to stock market prediction, or the collection of intelligence about military and government movements. Typically, these applications require knowledge about the metadata of the aircraft, specifically its operator and the aircraft category.